Experimental investigations of indoor air particular matter in hot and humid climates - Wongwatcharapaiboon, Jitiporn (2017)
Throughout the era of globalization, industrial development and transportation have brought about hazardous air environment especially in developing countries. Southeast Asia with large number of labor and natural sources has expanded manufacturing area as well as the problem of local community being reluctant air pollutant. It seems to be double suffocation with emitting frequently forest fire fume covering some parts of Thailand and Indonesia. These reasons can lead to around 5-time exceeding of annual standard in the National Ambient Air Quality Standards (NAAQs). Without fresh ventilation, filtration has become more important but it may be not affordable for low income people. So this study aims to develop low cost air dust purifier being suitable for hot and humid climate based on NAAQs and BS EN. Based on low cost and general air purifying techniques, fabric filter and solid fibre mop were selected for air cleaning efficiency evaluation in laboratory. For fabric filter, in one cubic meter wooden box, pleated fabric filter was installed in the middle of box and body spray was sourced as air particulate matter sized 2.5 micron (PM2.5). The result demonstrates air cleaning efficiency of fabric filter at 85% with high fan speed. This is equal F7 in BS EN and MERV 16 in NAAQs for fine dust filtration. Turning to solid fibre mop evaluation, mops with several sizes of fibre diameter in particular (A) 0.08-0.58 mm, (B) 0.22 mm and (C) 0.16 mm were installed in the middle of box sized 0.41 m width, 0.51 m length and 0.45 m height. The results show the highest efficiency to clean PM2.5 and PM10 at 36% in mop C and 25% in mop B respectively. Moreover, multiple mops C and A have high rapidity of air PM2.5 removal at 0.050 mg/sec in 300 seconds; while multiple mops B and C have high rapidity of air PM10 removal at 0.005 mg/sec in 300 seconds. According to performance to clean PM2.5 and PM10, mop B with TiO2 coating on solid fibre was selected to integrate within filter lamp. Environmental factors are found to affect PM2.5 concentration in different trend. Temperature responded negatively; while relative humidity provided positive relationship to PM2.5 concentration. In most case of solid fibre mops tests, relative humidity dropped PM2.5 removal efficiency, but increase PM10 removal efficiency. However, high relative humidity and temperature in the filter lamp tests were set high as same as in tropical climate. After laboratory tests, fabric filter was combined within floor lamp as lamp shade and solid fibre mop was set in the middle core of lamp with coated TiO2 2.0% concentration and UV light bulb. Fan unit was set in the bottom of lamp in order to control system flow speed in application system. The application was placed in 2.5x2.5x2.5 m3 bedroom for cleaning indoor PM2.5 in six different algorithms comparing to existing PM2.5 concentration. The best efficiency of PM2.5 removal is 99.07% of regime F with fabric filter, TiO2 coating mop and fan speed at 3 m/s. This is also ranked into F9 in BS EN and MERV16 in NAAQs for fine dust cleaning filtration. Without photocatalytic process in regime B, C and D, the application could be used in lower efficiency. Higher fan speed was substantial effect on PM2.5 removal efficiency and rapidity for filter lamp. This filter lamp was found high efficiency to clean indoor PM2.5 in hot and humid condition. Based on low cost development, this application can be applied with natural ventilation system in buildings in Southeast Asia hot and humid climate. Also other conditional climate buildings may integrate this application with lower air cleaning efficiency.